The effects of the integrative strategy on fostering reflective thinking and imparting basic basketball offensive techniques to female students - Missaa Nadem; Nadeema Badr Mohammed; Huda Badwe Shbeeb; Iqbal Abdul Hussein Neamah; Najlaa Abbas AL-Zuhairi; Nihad Mohammed Alwan (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Objective: The objective of this study is to develop instructional materials that teach fundamental basketball skills to female students enrolled in the first year of the College of Physical Education and Sports Sciences for Girls at the University of Baghdad while also encouraging reflective thinking (RT).